2011
DOI: 10.1063/1.3655678
|View full text |Cite
|
Sign up to set email alerts
|

Extremely high absolute internal quantum efficiency of photoluminescence in co-doped GaN:Zn,Si

Abstract: Determination of the absolute internal quantum efficiency of photoluminescence in GaN co-doped with Si and Zn J. Appl. Phys. 111, 073106 (2012); 10.1063/1.3699312 GaN/Al0.5Ga0.5N (11-22) semipolar nanostructures: A way to get high luminescence efficiency in the near ultraviolet range J. Appl. Phys. 110, 084318 (2011); 10.1063/1.3654053 Hole carrier concentration and photoluminescence in magnesium doped InGaN and GaN grown on sapphire and GaN misoriented substrates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…It is worth noting that our internal quantum efficiency can be significantly improved when the doping is optimized. A previous study indicated that the internal quantum efficiency can reach 93% in ref 29. To confirm that the ASPL of GaN is indeed a phononassisted phenomenon, we have measured the intensity of ASPL as a function of the pump power.…”
mentioning
confidence: 85%
“…It is worth noting that our internal quantum efficiency can be significantly improved when the doping is optimized. A previous study indicated that the internal quantum efficiency can reach 93% in ref 29. To confirm that the ASPL of GaN is indeed a phononassisted phenomenon, we have measured the intensity of ASPL as a function of the pump power.…”
mentioning
confidence: 85%
“…On the other hand, GaN based diluted magnetic semiconductors (DMSs) fabricated by single-doping with transition metal (TM) or RE ions have been studied extensively, due to the fact that both charge and spin can be manipulated simultaneously in such materials [3][4][5][6][7]. Moreover, Reshchikov et al [8] obtained extremely high absolute internal quantum efficiency of photoluminescence in GaN films co-doped with Zn and Si. Baik et al [9] reported the high-T c ferromagnetism in GaN films, they claimed that the T c can be modified by co-implantation with Mn and N ions.…”
Section: Introductionmentioning
confidence: 98%
“…1. The experimentally fitted nonradiative capture rate ranges from 3 × 10 −6 cm 3 /s to 3 × 10 −10 cm 3 /s [5][6][7][8][9], highlight the importance of using ab initio method to clarify the situation.…”
mentioning
confidence: 99%
“…The synthesized GaN often contains unintentionally doped Zn impurity accompanying an characteristic blue shift in photoluminescence (PL) [5][6][7][8], and also a sharp drop in PL intensity, due to nonradiative decay. Although the exact nature of the nonradiative decay center is still under debat, it is suggested [5] that it could be Zn Ga V N , a Zn impurity site together with a N vacancy as shown in the inset of Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation